Critical period of crop sensitivity to water deficit stress in elephant foot yam (Amorphophallus paeoniifolius) - RAVI, V; SUJA, G; GEORGE, JAMES; NEDUNCHEZHIYAN, M; SARAVANAN, R; BYJU, G (The Indian Journal of Agricultural Sciences, 2015)
The effect of Water Deficit Stress (WDS) at different growth period on growth and productivity of Amorphophallus and the critical period of crop sensitivity to WDS was investigated during 2011-12 and 2012-13 with the variety Gajendra. Cut pieces of corm weighing 500 g were planted in RBD with four replications in the experimental plot of CTCRI. The treatments were, viz. T1 - Control (without water deficit stress), T2 - WDS during four and five months after planting, T3 - WDS during five and six months after planting and T4 - WDS during six and seven months after planting. Control plots were irrigated when the soil moisture was depleted to 50% of field capacity, whereas WDS was imposed by withholding water. The significant reduction in leaf area in WD stressed plants resulted in significant reduction in corm dry matter as well as corm yield per plant. Compared to control plants, the reduction in corm yield was 41.19% more due to WDS during 4-5 Months After Planting (MAP) (78.52%) than during 6-7 MAP (37.33%). The observed results indicate that WDS during 4 and 5 or 5 and 6 months crop growth period significantly affected growth and productivity of Amorphophallus. Apart from the initial establishment period and growth period between 4 and 6 months are critical and therefore crop must be irrigated adequately during these periods for achieving more corm yield.